Application of Mirror Therapy of the Face on Facial Muscle Ability in Stroke Patients at RST Dr. Soedjono Magelang - Ainnur Rahmanti (International Journal of Medicine and Health, 2023)
Stroke is a reduced blood flow and oxygen to the brain due to blockage, narrowing, or rupture of blood vessels. Stroke leading weakness of the face, according to damage in the frontal motor area. One way to overcome a facial weakness is to apply mirror therapy of the face which is a combination of mirror therapy and facial exercises. The purpose of this case study is to illustrate the application of facial mirror therapy in stroke patients with facial muscle abilities. This type of research is descriptive by using a case study approach. The subjects in this study were 2 stroke patients with the criteria for facial muscle weakness, which is having a sagging face, having a recurrent attack or having just had a stroke. The study showed that an increase in facial muscle ability in subject 1 from the sufficient category (score 21) to the good category (score 29), subject 2 from the sufficient category (score 24) to the good category (score 32). Recommendation : Nurses can apply Mirror Therapy of the Face to improve the ability of facial muscles in stroke patients.